The Deserted City - Sherman, Francis, 1871-1926 (Salt Lake City, UT : Project Gutenberg, 2013)
"The Deserted City" by Francis Sherman is a collection of stray sonnets, published in the late 19th century. This poetic work explores themes of love, loss, beauty, and the passage of time through a series of reflections and emotional expressions that resonate with the human experience. The book employs a variety of metaphors and imagery, inviting readers to mingle with the poet's meditative thoughts. In "The Deserted City," Sherman takes the reader on an introspective journey through various "houses," each representing different aspects of life and emotion. These houses include notions like doubt, mercy, love, and beauty, creating a tapestry of sonnets that reflect the complexity of human emotions and their intertwined nature. As the speaker grapples with memories and desires, the poetry weaves together the joys and sorrows of existence, revealing the rich inner life of an individual seeking solace amidst the silent echoes of the past. The collection culminates in a poignant recognition of beauty and wisdom, as the speaker contemplates the enduring nature of love and the transient quality of life itself. (This is an automatically generated summary.)
The house of night -- The house of doubt -- The house of mercy -- The house of earth -- The house of faith -- The house of tears -- The house of love -- The house of beauty -- The house of content -- The house of change -- The house of regret -- The house of wisdom -- The house of sin -- The house of music -- The house of colour -- The fourth day -- Victory -- The last storm -- A last word.
Release date is 2013-05-08
Produced by Al Haines
Keywords: Canadian poetry; Sonnets